NETosis as Source of Autoantigens in Rheumatoid Arthritis - Corsiero, Elisa; Pratesi, Federico; Prediletto, Edoardo; Bombardieri, Michele; Migliorini, Paola (Frontiers in Immunology, 2016)
In neutrophils (but also in eosinophils and in mast cells) different inflammatory stimuli, induce histone deimination, chromatin decondensation and NET formation. These web-like structures that trap and kill microbes contain DNA, cationic granule proteins and anti-microbial peptides, but the most abundant proteins are core histones. Histones contained in NETs have been deiminated and arginines are converted in citrullines. While deimination is a physiological process amplified in inflammatory conditions, only individuals carrying genetic predisposition to develop rheumatoid arthritis (RA) make antibodies to deiminated proteins. These antibodies, collectively identified as anti citrullinated proteins antibodies (ACPA), react with different deiminated proteins and display partially overlapping specificities. In this paper, we will summarize current evidence supporting the role of NETosis as critical mechanism in the breach of tolerance to self-antigens and in supporting expansion and differentiation of autoreactive cells. In fact, several lines of evidence connect NETosis with RA: RA unstimulated synovial fluid neutrophils display enhanced NETosis; sera from RA patients with Felty’s syndrome bind deiminated H3 and NETs; a high number of RA sera bind deiminated H4 contained in NETs; human monoclonal antibodies generated from RA synovial B cells decorate NETs and bind deiminated histones. In RA, NETs represent on one side an important source of autoantigens bearing post-translational modifications and fuelling the production of ACPA. On the other side, NETs deliver signals that maintain an inflammatory milieu and contribute to the expansion and differentiation of ACPA-producing B cells.